Pengaruh Brand Authenticity Dan Store Atmosphere Terhadap Revisit Intention Pada Singgah Coffee And Eatery Padang - Zandy Armeto; Rian Surenda (Lembaga Pengembangan Kinerja Dosen, 2024)
The findings of phenomena related to brand authenticity, store atmosphere, and revisit intention at Singgah Coffee and Eatery Padang are the driving force behind this research. The purpose of this study is to examine how revisit intention at Singgah Coffee and Eatery Padang is influenced by brand authenticity and store atmosphere. This type of research uses a survey method with a causal associative quantitative approach to examine cause and effect. The population is Singgah Coffee and Eatery Padang customers. A total of 97 respondents were sampled in this study, using non-probability sampling techniques through purposive sampling method. The Likert scale was used to assess the validity and reliability of the questionnaire used as a data collection tool. SPSS 26.00 was used to process the research data. This study shows the results of brand authenticity and store atmosphere have a significant effect on revisit intention at Singgah Coffee and Eatery Padang.